Evaluation of Changes in a Suboptimal Economy - Rohlfs, Jeffrey (Review of Economic Studies, 1976)
Journal Article Evaluation of Changes in a Suboptimal Economy Get access Jeffrey Rohlfs Jeffrey Rohlfs Stanford University and Bell Laboratories Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 43, Issue 2, June 1976, Pages 359–362, https://doi.org/10.2307/2297331 Published: 01 June 1976